Bronchial complications after lung transplantation - I. V. Pashkov (Vestnik Transplantologii i Iskusstvennyh Organov, 2021)
Bronchial complications are among the main causes of impairing postoperative period and thansplant failure. Severe bronchial complications are very rare but have a high mortality rate. Light forms decrease transplant function and while progressing can leads to life-threatening conditions without required treatment. Nowadays there is a huge necessity in classification of diagnostic and bronchial complications treatment on different terms after lung transplantation. Methods of observation bronchoscopy and interventional bronchology are allowing us to realize prevention, diagnostic and treatment bronchial complications.